SMS GATEWAY-BASED EARLY FLOOD DETECTION WARNING SYSTEM DESIGN - Shindy Ramadhani; Nadya Andhika Putri; Indri Sulistianingsih; Eko Hariyanto (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
Natural disasters that are familiar and often occur around the world, including our country Indonesia one of which is flooding, and not infrequently this also often occurs at night and when the home occupier is not in a place that usually often causes material losses and not infrequently also causes fatalities. This study aims to implement a prototype system that allows to know the possibility of flooding before water enters the area or area of people's homes by using alerts in the form of alarm sounds or sms messages. Which is where this flood-cutting early warning prototype system will use Arduino as a microcontroller that will thoroughly control the ultrasonic sensor as a water level detector and buzzer sensor as a sounder or alarm when the water level has reached a certain limit, Where sms will be directly sent by the SENSOR SIM800L to the citizen's mobile phone or contact number that has been adjusted by the system. So the final result of this small study is that a prototype system of early warning of SMS Gateway-based flood detection will be very helpful for residents to know how the water level will be when entering people's homes.